Analysis of the bond interface between self-adhesive resin cement to eroded dentin in vitro - Moda, Mariana Dias [UNESP]; Fagundes, Ticiane Cestari [UNESP]; Briso, André Luiz Fraga [UNESP]; Santos, Paulo Henrique dos [UNESP] (Public Library of Science (PLoS), 2018)
The purpose of this study was to evaluate the bonding interface between a self-adhesive resin cement to in vitro eroded dentin. Seventy-two third molars were used and divided into two groups: sound dentin and in vitro eroded dentin. The in vitro erosion was performed following a demineralization protocol, in which the specimens were immersed in a demineralizing solution for 2 minutes per cycle and remineralizing solution for 10 minutes per cycle for 9 days. Both groups were submitted to four dentin surface treatments: control group (without any treatment), 2% chlorhexidine, 20% polyacrylic acid, and 0.1 M EDTA (n = 9). Blocks of resin-based composite were bonded with RelyX U200 self-adhesive resin cement applied on the pretreated dentin surfaces. The teeth were sectioned into beams (1mm 2 ) and submitted to microtensile bond strength testing to evaluate the bond strength of self-adhesive resin cement to dentin after 24 hours and 8 months of immersion in artificial saliva. Three specimens of each group were longitudinally cut and evaluated using confocal laser scanning microscopy to analyze the dentin/cement interface. Eroded dentin showed higher bond strength values when compared to sound dentin for the 2% chlorhexidine group (p = 0.03), 24 hours after adhesion. When considering eroded dentin, the 0.1M EDTA group showed higher bond strength values with a statistically significant difference only for the control group (p = 0.002). After 8 months of storage, the present results showed that there was no statistically significant difference between the two substrates for all experimental groups (p>0.05). Analysis of the microscopy confocal showed different types of treatments performed on dentin generally increased tags formation when compared to the control group. The eroded dentin showed a significant increase in density and depth of resinous tags when compared to sound dentin. The storage of samples for 8 months seems to have not caused significant degradation of the adhesive interface.